The Influence Of Demographic Factors And Financial Literature On Students' Investment Perceptions - Ariel Jotham Luther; sumani sumani (AIBPM Publisher, 2023)
Several factors influence how these decisions are made in making investment decisions, such as demographic and financial literacy. Financial literacy can provide insight into managing personal finances and give the public about formal financial institutions and financial services. Demographic factors such as age, gender, and education can also influence investment decisions. The purpose of this study was to analyze the influence of demographic characteristics, namely gender, faculty and cumulative achievement index (GPA), and financial literacy, on student investment decisions in the city of Jakarta, Bogor, Depok Tangerang, and Bekasi. We conducted this research by distributing questionnaires through Google forms and social media to active students from all universities in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The number of samples in this study amounted to 130 respondents. The research method uses descriptive statistics, validity, and reliability tests. Then proceed with the classical assumption, normality, heteroscedasticity, and multiple regression analysis tests, namely T-test and F test. The data processing results indicate that gender does not affect student investment decisions while faculty, cumulative achievement index (GPA), and financial literacy significantly influence student investment decisions.Â Â .Â